Extraction of Chitin, Chitosan, and Calcium Acetate from Mussel Shells for Sustainable Waste Management - Chaowared Seangarun; Somkiat Seesanong; Banjong Boonchom; Nongnuch Laohavisuti; Pesak Rungrojchaipon; Wimonmat Boonmee; Sirichet Punthipayanon; Montree Thongkam (International Journal of Molecular Sciences, 2025)
O) similar to synthesized calcium acetate in previous research. In addition, the mineral contents of calcium acetate identified by X-ray fluorescence (XRF) analysis exhibit 97.8% CaO with non-toxic impurities. This work demonstrated the potential of the production process of chitin, chitosan, and calcium acetate for the development of a sustainable industrial process with competitive functional performance against the commercial chitin and chitosan production process using crustacean shells and supported the implementation of a circular economy.
Keywords: Nanocomposite Films for Food Packaging; biodegradable polymer synthesis and properties